CFD Study of Influence of the Drift Angles on the Flow Properties Around DARPA Suboff Submarine with the Propeller - عفيف, أمارة; نوار عباس , (Latakia University Journal -Engineering Sciences Series, 2024)
This research calculates and analyzes the flow around the DARPA Suboff submarine using a Computational Fluid Dynamics (CFD) technique. It was focused on the flow at different sailing conditions (at the straight course and different drift angles), the resistance affecting the submarine during sailing was calculated, as well as the pressure distribution on the hull surface and the velocity distribution in the propeller plane at different situations (DARPA alone, DARPA with fins, DARPA with fins and propeller and DARPA with propeller without fins). The RANS method and k-ω Shear Stress Transport (SST) model with the ANSYS program were used to solve the Navier-Stokes equations. The numerical results were compared with experimental data. This Comparison showed how accurate CFD technology is in calculating this type of flow case.